2020
DOI: 10.3390/polym12020342
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Dissolution of Cellulose in NaOH as “Seen” by X-rays

Abstract: Cotton production is reaching a global limit, leading to a growing demand for bio-based textile fibers produced by other means. Textile fibers based on regenerated cellulose from wood holds great potential, but in order to produce fibers, the components need to be dissolved in suitable solvents. Furthermore, the dissolution process of cellulose is not yet fully understood. In this study, we investigated the dissolution state of microcrystalline cellulose in aqueous NaOH by using primarily scattering methods. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It has also been suggested that the cellulose might not be molecularly dissolved in NaOH, but that it aggregates in solution already at low concentrations, as investigated by scattering methods [3]. There are however conflicting reports about the state of the cellulose in NaOH (aq), which suggests that the cellulose is sensitive to the preparation method and handling of the solutions [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that the cellulose might not be molecularly dissolved in NaOH, but that it aggregates in solution already at low concentrations, as investigated by scattering methods [3]. There are however conflicting reports about the state of the cellulose in NaOH (aq), which suggests that the cellulose is sensitive to the preparation method and handling of the solutions [4].…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that NaOH alone can increase the stress at break of the paper. It is known from the literature that NaOH alone can dissolve a small amount of cellulose (Martin-Bertelsen et al 2020). Therefore, we speculate that the increase in the stress at break of paper may be related to the partial dissolution of cellulose.…”
Section: Effect Of Treatment Temperature Thiourea Ratio and Treatment Time On Tensile Properties Of Papermentioning
confidence: 74%
“…With this as a starting point, SAXS results revealed that in the dissolved state, prior to gelation (sample S1), the cellulose chains were dissolved in a rather stiff conformation, as reported previously. 60 Fitting a cylinder model 61 to sample S1 (Figure 3d) yielded a radius of 0.28 nm and length of 16 nm, indicating individually dissolved cellulose chains with straight segments of (approximately 30 glucose units). The gelation showed up in the SAXS intensities as an increased contribution of low values of the scattering vector q (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%